Preliminary Report of Industrial Commission - F. W. T. (Quarterly Journal of Economics, 1900)
Preliminary Report of Industrial Commission F. W. T. F. W. T. Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 14, Issue 3, May 1900, Pages 430–432, https://doi.org/10.1093/qje/14.3.430 Published: 01 May 1900